2010
DOI: 10.1016/j.jvs.2009.12.033
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of 50 Surgically Managed Penetrating Subclavian Artery Injuries

Abstract: Objective: To evaluate the usefulness of systematic coronary angiography followed, if needed, by coronary artery angioplasty (percutaneous coronary intervention (PCI)) on the incidence of cardiac ischaemic events after carotid endarterectomy (CEA) in patients without evidence of coronary artery disease (CAD).Materials and methods: From January 2005 to December 2008, 426 patients, candidates for CEA, with no history of CAD and with normal cardiac ultrasound and electrocardiography (ECG), were randomised into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…4 Sobnach et al reviewed 50 patients who underwent surgical repair of subclavian artery injury, of which 24% had concomitant venous injury. 5 Our review of a larger multicenter trauma database showed a lower combined arterial and venous ASVI of 16%, which is more comparable to the experience of Demetriades and Asensio (20%). 1 It has been shown that venous injury portends a greater mortality risk than isolated arterial injury.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…4 Sobnach et al reviewed 50 patients who underwent surgical repair of subclavian artery injury, of which 24% had concomitant venous injury. 5 Our review of a larger multicenter trauma database showed a lower combined arterial and venous ASVI of 16%, which is more comparable to the experience of Demetriades and Asensio (20%). 1 It has been shown that venous injury portends a greater mortality risk than isolated arterial injury.…”
Section: Discussionsupporting
confidence: 69%
“…Combined injuries did not lead to differences in complications or most outcomes, with the exception once again being death. Blunt combined injuries had a statistically significant increase in 5). Penetrating injury also carried a higher mortality risk than blunt injury (OR, 1.96; CI, 1.03 to 3.73; p ¼ 0.041).…”
Section: Resultsmentioning
confidence: 94%
“…52 Concern for brachial injury if washout is not performed may not bear out-in one study where all 8 patients were managed with stents despite hemodynamic instability or hematoma, only 1 required a washout. 52 Lesions treated within the literature include occlusions, 54 dissections, 48,52,[55][56][57] pseudoaneurysm, 48,58,59 and arteriovenous (AV) fistulas 49,60 due to trauma. There are multiple reports of trauma secondary to iatrogenesis as well, which can present as AV fistulas and pseudoaneurysms.…”
Section: Abdominal Aortamentioning
confidence: 99%
“…17,18 Vascular repair may require extensive paraclavicular incisions for control; dissection though hematoma-distorted planes is feasible but not without a significant risk of neurovascular injury and significant hemorrhage. 21 In comparison, endovascular treatment is a safe and attractive alternative to conventional surgery in trauma patients.…”
Section: Discussionmentioning
confidence: 99%